بيانات عقد النقل البحري للبضائع "سند الشحن" - النعيمي، يحيى سعيد ناصر (محمد قاسمي, 2022)
إن أهمية سند الشحن البحري الذي يعد أهم أشكال عقد النقل البحري وأوسعها انتشارا، والذي يتعدى دوره بأنه إثبات على وجود العقد فقط، بل ويصل إلى حد اعتباره ملكية تداول للبضائع، لذا قام الباحث بداية بتحديد ماهية سند الشحن البحري؛ من خلال تحديد مفهوم سند الشحن البحري في التشريع المغربي والتشريع القطري والاتفاقيات الدولية، ثم عرج الباحث على تناول بيانات عقد النقل البحري، وحيث كان سند الشحن يقترب من الأورق المالية فعرج الباحث إلى البحث والتحليل في أشكال وثيقة الشحن البحري وما ذهب إليه الفقهاء من اختلافات. The importance of the waybill, which is the most important form of the contract of carriage of goods by sea and the most widely used, and whose role goes beyond the mere proof of the existence of the contract, and even goes as far as considering it as the property of the movement of goods. Thus, the researcher first determined the nature of the maritime bill of lading; By defining the concept of the maritime bill of lading in the Moroccan legislation, Qatari legislation and international conventions, then the researcher turned to the data of the maritime transport contract, and where the bill of lading was close to the securities, the researcher went to research and analysis in the forms of the maritime transport document and the differences on which the lawyers went.
Keywords: النقل البحري -- البضائع المشحونة -- الأوراق التجارية -- الاتفاقيات الدولية -- التشريعات العربية